Analysis of Concept Understanding in Material Colligative Properties of Solutions in View of the Tendency of Student Learning Styles at SMA N 1 Gunung Talang - Sukma, Nabilla; Latisma Dj, Latisma Dj; Ranti, Leny (Journal of Educational Sciences, 2023)
Education is an important thing in achieving the goal of ability through the learning process in the classroom. Benchmarks for the success of the learning process are seen through students' understanding of concepts. The influencing factor in understanding the concept is learning style, because learning style influences the maximum a person absorbs information. This research is a descriptive research aimed at analyzing and describing (1) understanding of the concept of colligative properties of the solution, (2) learning styles of students, (3) understanding of the concept of colligative properties of solutions in terms of the tendency of students' learning styles. The subjects of this study were class XII MIPA 1 SMA N 1 Gunung Talang, which consisted of 35 people. The instruments used in this study were the Kolb model learning style questionnaire and open-ended questions. The results of the research data analysis show that (1) the learning style of students in class XII MIPA 1, the assimilation learning style is 51.4%, the divergent is 22.9%, the convergent is 17.1%, and the accommodation is 8.6%, ( 2) Students' understanding of the concept of colligative properties of solutions is in the partial understanding category (3) Understanding of concepts in colligative properties of solutions in terms of the tendency of students' learning styles for convergent, divergent, and accommodation learning styles is in the understand category, and assimilation learning styles are in the partially understood category.